1997
DOI: 10.1016/s1010-7940(96)01114-1
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord protection using hypothermic cardiocirculatory arrest in extended repair of recoarctation and persistent hypoplastic aortic arch

Abstract: The use of hypothermic cardiocirculatory arrest in this special indication is a safe method which allows open reconstruction of the coarctation site and the aortic arch and protection of the spinal cord. The need for early reoperation because of inadequate repair may be reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 30 publications
0
7
0
2
Order By: Relevance
“…Spinal cord complications can be devastating after CoA repair in older patients who are thought to have inadequate collaterals . Partial left heart CPB or CPB with circulatory arrest is helpful to prevent paraplegia. Currently, a partial left heart bypass through a left thoracotomy is also required for urgent device retrieval after embolization of percutaneous implanted devices in the descending aorta .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spinal cord complications can be devastating after CoA repair in older patients who are thought to have inadequate collaterals . Partial left heart CPB or CPB with circulatory arrest is helpful to prevent paraplegia. Currently, a partial left heart bypass through a left thoracotomy is also required for urgent device retrieval after embolization of percutaneous implanted devices in the descending aorta .…”
Section: Discussionmentioning
confidence: 99%
“…Wong et al used a left heart bypass with a centrifugal pump cannulating the left pulmonary vein and the descending aorta distal to the coarctation. Lange et al reported using CPB and hypothermic circulatory arrest to repair a re‐coarctation. Circulatory arrest is not usually required for most patients with CoA or recurrent CoA.…”
Section: Discussionmentioning
confidence: 99%
“…Aortic repair is usually demanding, which increases the risk of bleeding and paraplegia. Therefore, deep hypothermic circulatory arrest may be advocated [4]. In this setting, extra-anatomic bypass is a reasonable option in order to lessen surgical risk, eventually permitting simultaneous treatment of cardiac problems and to promote a sustained long-term distal aortic perfusion [5].…”
Section: Discussionmentioning
confidence: 99%
“…The safety limit for aortic occlusion in the presence of distal hypotension is around 20 minutes. 19 As a result, a predicted long cross-clamp time in complex aortic reconstruction elevates the potential need for cardiopulmonary bypass. In our study, the mean aortic cross-clamp time was 41.3 6 17.1 minutes (range, 16-64 minutes).…”
Section: Indications To Use Cardiopulmonary Bypass In Aortic Coarctatmentioning
confidence: 99%